Görsel iletişim açısından film afişlerinin grafik çözümlemeleri (2000-2010 yılları arasında Antalya altın portakal film festivalinde ödül alan sinema film afişlerinin değerlendirilmesi) - Kavuran, Tamer; Cetinkaya, Ali (My University, 2012)
Tecnological developments, the improvements on printing techniques and the improvements that occur on publications have been effective on art elements of poster designing. As a result, poster designing; as a visual communication means, has gained a great importance more than ever. Between the years 2000-2010 held in Antalya Golden Orange Film Festival, winning the first place of the movie posters, this research examined the index contains a list of scientific publications on the subject and tried to be described with a screening of extracts. Descriptive findings from the data obtained these posters are graphically analyze in terms of visual communication.Given the content of these posters graphics products, the design should be more careful with the results of this research have emerged, and these results are in line with recommendations.
Bildiri - Yayımlanmış
Keywords: Poster; Visual communication; Film; Golden Orange; Graphic; Design